Language Rights - A Welfare-Economics Approach - Bengt-Arne Wickström (Center for Economic Studies and ifo Institute (CESifo), 2015)
Distributions of language rights in multilingual settings are analyzed from a normative viewpoint in this chapter. If the cost structure of providing rights is concave in the number of beneficiaries, then a critical-mass criterion for the determination of an optimal rights structure results. It is further shown that an efficiency analysis based on a `naive' cost-benefit calculation has to be augmented in various ways if rights influence the status of a language, which in turn influences the preferences for language rights. Also the inter-generational transfer of language repertoires to the next generation leads to an endogeneity of preferences. The endogeneity of preferences in turn can make the cost-benefit analysis contradictory. In a welfare-maximizing approach, redistribution goals further modify the analysis.
Keywords: D61; D63; H59; K19; Z19; 330; efficiency; cost-benefit analysis; economic justice; changeable preferences; language rights; linguistic justice; language policy